1999
DOI: 10.1002/(sici)1099-0488(19991215)37:24<3512::aid-polb12>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Strain effects on physical gelation of crystallizing isotactic polypropylene

Abstract: Early stages of crystallization of polymers may be viewed as thermoreversible physical gelation in which molecular connectivity is introduced by crystallization. Effects of shear strain on the early stages of crystallization of a commercial isotactic polypropylene are studied by dynamic mechanical experiments. Shear creep with large strains (up to γ = 300) on the undercooled melt for short times (the time did not exceed 100 s) was followed by small amplitude oscillatory shear (SAOS) at a strain amplitude (γa =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 21 publications
3
87
0
Order By: Relevance
“…) corroborated the earlier observations, not only in PE but also in a variety of other polymers, such as iPP, 43,44,50,[52][53][54][55][56][57][70][71][72][73][75][76][77][78] isotactic poly-1-butene (iPB), 90 polyethylene terephthalate (PET), 91 polydiethylsiloxane (PEDS), 91 etc. In some report, the quasicrystallographic flowinduced structures are referred to as ''mesophase.''…”
supporting
confidence: 85%
See 1 more Smart Citation
“…) corroborated the earlier observations, not only in PE but also in a variety of other polymers, such as iPP, 43,44,50,[52][53][54][55][56][57][70][71][72][73][75][76][77][78] isotactic poly-1-butene (iPB), 90 polyethylene terephthalate (PET), 91 polydiethylsiloxane (PEDS), 91 etc. In some report, the quasicrystallographic flowinduced structures are referred to as ''mesophase.''…”
supporting
confidence: 85%
“…It was shown that a fraction of PE molecules adopted all-trans sequence configurations upon shearing, which remained stable for several hours even after cessation of shear. The recent results of the techniques that couple flow (parallel plate, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]66,68,[74][75][76][77][78] fiber pullout, 14,79,80 die extrusion 15,[70][71][72][73][81][82][83] ) with a physical probe of the structure development (transmitted light, [70][71][72][73][81][82][83] optical microscopy, 14,[75][76][77][78]79,80 X-ray diffraction, 42-57 atomic force microscopy, …”
mentioning
confidence: 99%
“…One could think of using other approaches by applying more simple models (Boutahar et al 1996(Boutahar et al , 1998Tanner 2002Tanner , 2003van Ruth et al 2006) or empirically based scaling laws between the space filling and the storage modulus (see Coppola et al 2006;Khanna 1993;Pogodina et al 1999). However, it was demonstrated in Steenbakkers and Peters (2008) that such approaches do perform less than the suspension model as used here, and therefore, we will not apply them to our results.…”
Section: Discussionmentioning
confidence: 99%
“…The wellknown Kolmogorov-Avrami equation [56,57] accurately captures the crystallization kinetics of spherulites, even when their number density is strongly increased by flow [35,58]. However, for shish-kebab structures, in-situ XRD has revealed that the Avrami model often fails [49,[59][60][61].…”
Section: State Of the Artmentioning
confidence: 99%
“…The most straightforward way of implementing the proposed effect, requiring the least number of adjustable parameters, is to adjust the viscosity of the material via the modulus. Therefore, following Pogodina et al [58], we express the moduli of the material as…”
Section: Structure Formationmentioning
confidence: 99%